A Finite-Volume Method for Nonlinear Nonlocal Equations with a Gradient Flow Structure. (28th November 2014) - Carrillo, José A.; Chertock, Alina; Huang, Yanghong
Abstract: We propose a positivity preserving entropy decreasing finite volume scheme for nonlinear nonlocal equations with a gradient flow structure. These properties allow for accurate computations of stationary states and long-time asymptotics demonstrated by suitably chosen test cases in which these features of the scheme are essential. The proposed scheme is able to cope with non-smooth stationary states, different time scales including metastability, as well as concentrations and self-similar behavior induced by singular nonlocal kernels. We use the scheme to explore properties of these equations beyond their present theoretical knowledge.